Prevalence of myopia: A large-scale population-based study among children and adolescents in weifang, china - Zhang, Jie; Li, Zhenhua; Ren, Jiantao; Wang, Wenting; Dai, Jiazhen; Li, Cong; Huang, Xudong; Sun, Xianyong; Liu, Lei; Wang, Chunping (Frontiers in Public Health, 2022)
Purpose: To determine the prevalence of myopia among school-aged children and adolescents at the whole city level of Weifang, China. Methods: This study was a large scale school-based cross-sectional study among children and adolescents aged 5 to 20 years old. Participants were selected by school based registration system in 2020. All the subjects underwent spherical equivalent (SE) error with noncycloplegic autorefraction measurement. Myopia was defined as a SE refraction of ≤ −0.75 diopters (D) and graded into low myopia (-0.75 to -3.00 D), moderate myopia (-3.01 to -5.99 D) and high myopia (≤ -6.00 D). Results: A total of 1,059,838 participants were eligible for this survey and 1,013,206 (95.6% participation rate) were selected through data quality control, which comprised 17 districts/counties and 1,254 schools including 861 elementary schools, 313 middle schools and 80 high schools. The mean age of participants was 11.57 ± 3.36 years (5 - 20 years), and the male to female ratio was 1.11. The whole city levels` prevalence of total myopia was to be 75.35%. The prevalence of total myopia among the students in Hanting was 45.47%, but approximately 82.37% students living in Changyi have myopia. The overall prevalence of low myopia in elementary, middle, and high school students was 48.56%, 47.30%, and 31.62%, respectively, while the high myopia (SE ≤ -6.00D) prevalence was 1.12%, 8.89%, and 20.12%, respectively. The overall prevalence of myopia increased fastest from 7 to 9 years old. The prevalence of high myopia was 7.59% for girls and 6.43% for boys, respectively (P<0.001). The prevalence of myopia increased with age and grade increasing, but SE decreased with age and graded increasing. Conclusions: Current investigation demonstrated a high proportion of myopia among school students in the city of Weifang, and gradually increased with age, and the prevalence of myopia was highest in Changyi areas. The high myopia prevalence for girls was higher than that in boys.